Beacon Hill The Life and Times of a Neighborhood - Li-Marcus, Moying (Northeastern University Press, 2019)
An insightful study of urban transformation recalls four centuries in the life of Boston's most famous neighborhood, tracing social, economic, and political changes in the community. Originally published by Northeastern University Press in 2002. With a new foreword by Jeffrey E. Klee.